Oral Vaccination With a Formulation Combining Rhipicephalus microplus Subolesin With Heat Inactivated Mycobacterium bovis Reduces Tick Infestations in Cattle - Contreras, Marinela; Kasaija, Paul D.; Merino, Octavio; de la Cruz-Hernandez, Ned I.; Gortazar, Christian; de la Fuente, José (Frontiers in Cellular and Infection Microbiology, 2019)
Vaccines are an environmentally friendly alternative to acaracides for the control of tick infestations, to reduce the risk for tick-borne diseases affecting human and animal health worldwide, and to improve animal welfare and production. Subolesin (SUB, also known as 4D8) is the functional homolog of Akirin2 involved in the regulation of development and innate immune response, and a proven protective antigen for the control of ectoparasite infestations and pathogen infection. Oral vaccination combining protein antigens with immunostimulants has proven efficacy with increased host welfare and safety, but has not been used for the control of tick infestations. Here we describe the efficacy of oral vaccination with a formulation combining Rhipicephalus microplus SUB and heat inactivated Mycobacterium bovis (IV) on cattle tick infestations and fertility. The levels of IgG antibody titers against SUB and M. bovis P22, and the expression of selected immune response genes were determined and analyzed as possible correlates of protection. We demonstrated that oral immunization with the SUB+IV formulation resulted in 51% reduction in the number of female ticks and 30% reduction in fertility with an overall efficacy of 65% in the control of R. microplus infestations by considering the cumulative effect on reducing tick survival and fertility in cattle. The akr2, IL-1β, and C3 mRNA levels together with antibody levels against SUB correlated with vaccine efficacy. The effect of the oral immunization with SUB+IV in cattle on tick survival and fertility is essential to reduce tick infestations, and extended previous results on the effect of R. microplus SUB for the control of cattle tick infestations. These results support the development of oral vaccines formulations for the control of tick infestations and the incidence of tick-borne diseases.